Molecular Genetics and Targeted Therapy in Hepatocellular Carcinoma - I. Marks, Eric; S. Yee, Nelson (Current Cancer Drug Targets, 2016)
Hepatocellular carcinoma (HCC) is a highly lethal disease, therefore effective and tolerable treatment is urgently needed. In this article, we provide an updated review of the genetic abnormalities and mechanisms that drive carcinogenesis of HCC, and discuss the targeted therapeutics that are being investigated in HCC. Hepatocellular carcinogenesis typically begins with chronic inflammation of hepatocytes that progressively transform into invasive carcinoma. These events are associated with molecular abnormalities and chromosomal alterations. Multiple analyses of HCC have revealed aberrant expression or activity of growth factors and receptors, and the associated signaling pathways. These molecular alterations are implicated in the development and progression of HCC, and they have been exploited as targets for therapy. Targeted agents that inhibit receptor tyrosine kinases and their downstream signal mediators, angiogenesis, and immunomodulators have been developed and clinically investigated. Among these targeted agents, the multi-kinase inhibitor sorafenib has become the standard treatment for advanced HCC, though its therapeutic benefit is limited. Continued research is essential for improving treatment response and minimizing toxicity for patients with HCC. Future investigation will need to focus on utilizing patterns of gene expression to classify HCC into groups that display similar prognosis and treatment sensitivity, and combining targeted therapeutics with conventional chemotherapy that produce enhanced anti-tumor effect. By integration of tumor profiling and targeted therapeutics in HCC, we hope to advance towards the goal of precision treatment for patients with this malignant disease.
Keywords: sorafenib